2018
DOI: 10.3390/v10080422
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics and Immunologic Tools: The Impact of Viral and Host Genetic Variations on the Outcome of Zika Virus Infection

Abstract: Zika virus (ZIKV) causes no-to-mild symptoms or severe neurological disorders. To investigate the importance of viral and host genetic variations in determining ZIKV infection outcomes, we created three full-length infectious cDNA clones as bacterial artificial chromosomes for each of three spatiotemporally distinct and genetically divergent ZIKVs: MR-766 (Uganda, 1947), P6-740 (Malaysia, 1966), and PRVABC-59 (Puerto Rico, 2015). Using the three molecularly cloned ZIKVs, together with 13 ZIKV region-specific p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 89 publications
1
38
0
Order By: Relevance
“…The effects of ZIKV infection seen during the first trimester in sheep are comparable to those observed in humans, as well as fetal outcomes caused by ovine infections; primarily fetal loss [19][20][21][22][23][24]. Furthermore, previous research indicates that the viral kinetics of ZIKV in fetal sheep cells has been shown to be similar to that in immortalized Aedes albopictus cells [26]. We have also demonstrated that immortalized adult sheep kidney cells and immortalized fetal sheep testicular cells are susceptible to ZIKV infection and can sustain viral replication for many days [25].ZIKV is also unique in that sexual transmission occurs with infection of the male reproductive tract with possible establishment of prolonged, asymptomatic infection in men [27][28][29][30].…”
mentioning
confidence: 86%
“…The effects of ZIKV infection seen during the first trimester in sheep are comparable to those observed in humans, as well as fetal outcomes caused by ovine infections; primarily fetal loss [19][20][21][22][23][24]. Furthermore, previous research indicates that the viral kinetics of ZIKV in fetal sheep cells has been shown to be similar to that in immortalized Aedes albopictus cells [26]. We have also demonstrated that immortalized adult sheep kidney cells and immortalized fetal sheep testicular cells are susceptible to ZIKV infection and can sustain viral replication for many days [25].ZIKV is also unique in that sexual transmission occurs with infection of the male reproductive tract with possible establishment of prolonged, asymptomatic infection in men [27][28][29][30].…”
mentioning
confidence: 86%
“…Similarly, all Asian lineage ZIKV strains, such as H/PF/2013 and PRVABC59, are glycosylated at N154, whereas some of the African lineage ZIKV strains are not (21)(22)(23). The prototype ZIKV strain includes both glycosylated and non-glycosylated variants, all designated "MR766", which can be a source of confusion in the literature (24)(25)(26). DENV is unique among flaviviruses in that its E protein contains two N-linked glycosylation sites, one at N67 and a second at N153, which are present in most strains of the four DENV serotypes (18,27,28).…”
Section: Flavivirus Envelope Protein Glycosylationmentioning
confidence: 99%
“…These include the insertion of a synthetic intron into the molecular construct, which is later removed upon splicing in mammalian cells [ 78 , 79 ], or the separation of the viral genome and generation of subgenomic fragments. Several approaches have been used to circumvent toxicity in bacteria including usage of low copy plasmids [ 80 ], usage of bacterial artificial chromosomes [ 81 ] and separation of the genome to disrupt toxic regions [ 82 , 83 ]. Furthermore, a more elaborated approach using a bacterium-free reverse genetic method called ISA (infectious subgenomic-amplicons) [ 84 ] based on the in vitro generation of overlapping subgenomic amplicons covering the ZIKV genome, subsequent transfection into susceptible host cells and recovery of recombinant virus by “in cellulo” recombination was applied [ 85 , 86 , 87 ].…”
Section: In Vitro Models and Screening Approachesmentioning
confidence: 99%
“…Interestingly, even though ZIKV was able to replicate efficiently in various cell lines, the amount of intracellular infectious particles, as well as virus release and extent of cytopathic effect varied among the cell lines tested [ 87 , 113 , 130 , 131 , 132 ]. Furthermore, it was shown that next to human, NHPs and murine cells, ZIKV is able to replicate within a wide range of animal cell lines, expanding the variety of cell lines that can be used to study ZIKV infections [ 81 , 130 , 133 ]. Given their usefulness regarding availability, cost and handling, cell lines offer a powerful tool for the identification and characterization of antivirals.…”
Section: In Vitro Models and Screening Approachesmentioning
confidence: 99%